The Effect of Business Center on Entrepreneurial Readiness for Vocational Students - Mafahir, Muhammad Alil; Rijanto, Tri; Munoto, Munoto; Nurlaela, Lutfiyah (International Journal for Educational and Vocational Studies, 2020)
In August 2017, there were 7.4 million educated unemployed including vocational graduates. Why are there so many educated unemployed. Are there no vocational high school (SMK) graduates who can become entrepreneurs? The Vocational High School is the right place to develop entrepreneurship education. This study aims to determine the extent of the influence of the Business Center that can increase vocational entrepreneurship readiness. This research was conducted through a literature review and relevant research results and continued through a Focus Group Discussion (FGD). The data analysis technique used is descriptive-qualitative analysis technique. The study found that the Business Center can increase the entrepreneurial readiness of vocational students, which means that increasing the entrepreneurial readiness of vocational students can be done through improving skills through the Business Center.